Legal Protection for Athletes Who Experience Death During A Competition - Dewi Agustin Fitriani; Nursa Aida Farzana; Rizky Calista Belindasari (Faculty of Law Universitas Negeri Surabaya, 2025)
Sports are activities that play an important role in maintaining health and improving quality of life, but also contain physical risks, especially in contact sports such as boxing. Boxing is known as a popular martial art, but it has a high risk of injury and death for athletes. This study discusses the legal aspects related to protection and liability for the death of boxing athletes in matches. Factors causing the death of boxing athletes include lack of physical and mental preparation, negligence in the use of protective equipment, and falsification of medical documents. Legal protection for athletes is regulated in Law No. 3 of 2005 concerning the National Sports System, which requires organizers to provide a safe environment and adequate medical facilities. Legal liability for the death of athletes can be imposed on the organizer, referee, manager, or ring doctor if they are proven to be negligent in meeting safety standards as regulated in Articles 52 and 103 of the Sports Law and Article 359 of the Criminal Code.